2015
DOI: 10.7250/mstct.2014.009
|View full text |Cite
|
Sign up to set email alerts
|

Technical Embroidery for Smart Textiles: Review

Abstract: -Traditionally embroidery is known as a conventional technique of textile decoration. Since the niche of technical textiles is rapidly expanding and is the main field of innovation and research in textile and apparel industry, embroidery is found in a variety of new functional applications due to the unique opportunity of creating three-dimensional light-weight structures and laying threads on the base material in all directions. As the field of smart textiles is vast per se and is associated with technical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…The results of these experiments confirm that making a thermopile from pure conductive textile yarns is possible, particularly from a single woven, braided, or knitted NiCF yarn. Unlike the thermocouple mentioned by Mecnika et al, 11 our thermocouple was made from a single conductive yarn etched at specific spots. This allows us to create multiple thermocouples formed in series (thermopile) on a single conductive yarn in order to get a higher voltage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these experiments confirm that making a thermopile from pure conductive textile yarns is possible, particularly from a single woven, braided, or knitted NiCF yarn. Unlike the thermocouple mentioned by Mecnika et al, 11 our thermocouple was made from a single conductive yarn etched at specific spots. This allows us to create multiple thermocouples formed in series (thermopile) on a single conductive yarn in order to get a higher voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Ziegler and Frydrysiak 10 published their research on using several conductive threads such as polyacrylonitrile (Nitril), steel staple fibers, silver-coated polyamide, and graphite, but they found that the thermocouples possessed low accuracy and sensitivity. Another approach has been explained in a review paper by Mecnika et al 11 According to them, a thermocouple can be created from two different conductive metal yarns by embroidery technique.…”
Section: Introductionmentioning
confidence: 99%
“…Another typology of fabric is the embroidery, a decoration of conductive patterns on finished textile surface. This technology is of interest in the field of smart textiles because of the possibility to lay the base material in all directions rather than in pre-defined ones [ 29 ]; because of this, an enhanced skin-electrode contact can be obtained [ 27 ].…”
Section: Textile Technologiesmentioning
confidence: 99%
“… ( a ) Double lockstitch embroidery. The upper thread can be conductive; ( b ) Tailored fiber placement (TFP) embroidery; useful for fixating of functional fibers [ 34 ]. …”
Section: Figurementioning
confidence: 99%